Performance of Vortex Turbines with Two-Stage Radial-Offset Runners - Aulia Fathurrohman; Muhamad Dwi Septiyanto; Solikin Andriyanto; Ari Prasetyo; Dominicus Danardono Dwi Prija Tjahjana; Syamsul Hadi (Universitas Sebelas Maret, 2025)
Gravitational water vortex turbines are environmentally friendly power generation systems that convert the energy of vortex water flow into mechanical energy using turbine runners. This study aims to analyze the effect of a two-stage configuration with varied radial runner positions and water discharge on turbine performance. Experiments were conducted using a low-speed water channel with a conical basin to generate vortex flow. Savonius-type runners were installed vertically in two stages with radial positions of 0.5, 0.6, and 0.7 relative to the basin radius. Each configuration was tested at several water discharge rates. The primary parameter measured was mechanical power output, which was obtained using torque sensors and rotational speed meters to provide precise data. Results showed that the radial position 0.5 produced the best performance, generating 12.28 watts in the first and 16.68 watts in the second. Runner position and water discharge directly influenced vortex stability and energy conversion efficiency. The two-stage configuration with optimal runner placement significantly improved system efficiency. These findings suggest that the two-stage vortex turbine design is promising for small-scale power generation in remote areas.